Multidrug Resistance in Cancer: Understanding Molecular Mechanisms, Immunoprevention and Therapeutic Approaches - Emran, Talha Bin; Shahriar, Asif; Mahmud, Aar Rafi; Rahman, Tanjilur; Abir, Mehedy Hasan; Siddiquee, Mohd. Faijanur - Rob; Ahmed, Hossain; Rahman, Nova; Nainu, Firzan; Wahyudin, Elly; Mitra, Saikat; Dhama, Kuldeep; et al. (Frontiers in Oncology, 2022)
Cancer is one of the leading causes of death worldwide. Several treatments are available for cancer treatment, but many treatment methods are ineffective against multidrug-resistant cancer. Multidrug resistance (MDR) represents a major obstacle to effective therapeutic interventions against cancer. This review describes the known MDR mechanisms in cancer cells and discusses ongoing laboratory approaches and novel therapeutic strategies that aim to inhibit, circumvent, or reverse MDR development in various cancer types. In this review, we discuss both intrinsic and acquired drug resistance, in addition to highlighting hypoxia- and autophagy-mediated drug resistance mechanisms. Several factors, including individual genetic differences, such as mutations, altered epigenetics, enhanced drug efflux, cell death inhibition, and various other molecular and cellular mechanisms, are responsible for the development of resistance against anticancer agents. Drug resistance can also depend on cellular autophagic and hypoxic status. The expression of drug-resistant genes and the regulatory mechanisms that determine drug resistance are also discussed. Methods to circumvent MDR, including immunoprevention, the use of microparticles, nanomedicine, and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas)9 technology, might result in better strategies for fighting cancer.